1998
DOI: 10.1021/jp981713v
|View full text |Cite
|
Sign up to set email alerts
|

New and Surprising Experimental Results from the Oxidation of Sulfinic and Sulfonic Acids

Abstract: Thiourea, (H2N)2CS, aminoiminomethanesulfinic acid, H2N(HN)CSO2H (AIMSA), and aminoiminomethanesulfonic acid, H2N(HN=)CSO3H (AIMSOA) are all oxidized by mild oxidizing agents to a sulfate and an organic residue. AIMSA and AIMSOA are the postulated intermediates in the oxidation pathway of thiourea to sulfate. The oxidation of AIMSOA is accompanied by a cleavage of the C−S bond to form sulfate. Surprisingly, freshly prepared solutions of AIMSOA are oxidized by the common oxidants (oxyhalogens and halogens) at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
3

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 27 publications
0
53
0
3
Order By: Relevance
“…The rate coefficient of this reaction cannot be determined from our experiments because k 14 and k 15 were found to be in total correlation with each other. As we fixed k 15 , a value of (1.2 Ϯ 0.1) ϫ 10 5 m -1 s -1 could be calculated for the rate coefficient. The result for this reaction is in agreement with an independent result, [18] although the rate coefficients differ by a factor of 50.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate coefficient of this reaction cannot be determined from our experiments because k 14 and k 15 were found to be in total correlation with each other. As we fixed k 15 , a value of (1.2 Ϯ 0.1) ϫ 10 5 m -1 s -1 could be calculated for the rate coefficient. The result for this reaction is in agreement with an independent result, [18] although the rate coefficients differ by a factor of 50.…”
Section: Discussionmentioning
confidence: 99%
“…[13] Some oxidation reactions of TDO have been controlled in acidic solutions. [14][15][16] The oxidations of TDO with chlorite ions, iodine, and bromine have been performed by Simoyi et al [15][16][17][18] Regrettably, the tautomerization of TDO, which seems to occur relatively slowly from (NH 2 ) 2 CSO 2 to NH 2 NHCSO 2 H [19,20] at low pH values, has so far not been taken into account in these reactions, though the two tautomers may have quite different reactivity towards chlorine dioxide and other chlorine-containing intermediates.…”
Section: Introductionmentioning
confidence: 99%
“…We also found that the presence of O 2 inhibits H 2 SO 4 production in ice, similar to Donaldson and Johnston's (1968) (Vairavamurthy and Zhou 1995), and sulfinic acid, SO 2 H 2 (DellaGuardia and Johnston 1980), as intermediates. SO 2 H 2 is produced in low temperature (12 K) photolysis (Fender et al 1991) and sulfinic acids are oxidized to sulfate (Makarov et al 1998). The final step, hydration of sulfuric acid, is highly exothermic and may occur simultaneously with three-body oxidation reactions.…”
Section: Oxidants and Reaction Pathwaysmentioning
confidence: 99%
“…Предложенный механизм согласуется с кинетическими данными, приведенными в литературе [59,60,62] для реакции окисления 2-имино-4-тиобиурета кислыми иодатами и броматами.…”
Section: Itsunclassified
“…В литературе [60][61][62] авторы показали, что усиление окислительной способности реагента приводит к раскрытию пятичленного цикла с последующим образованием моно-, ди-и триоксида серы, в результате чего образуется гуанилмочевина. Этот вывод подтверждается результатами, описанными в работе [63] .…”
Section: синтез 35-диамино-124-тиадиазолаunclassified